Examining and mitigating sexual misconduct in sport - Prewitt-White, Tanya; Fisher, Leslee A. (Routledge, 2022)
Calling all sport constituents : exploring power and bringing joy back into sport / Leslee A. Fisher and Allison D. Anders -- Stand up and stand tall: rethinking sexual misconduct in sport / Robert E. Owens -- Cisheterosexism and sexual misconduct in sport / Travis R. Scheadler, Bernadette "Bernie" Compton, and Emma D. Kraus -- Grooming and sport / Stiliani "Ani" Chroni and Anna Kavoura -- Sexual misconduct and epistemic injustices in sport / Lindsey A. Miossi and Lars Dzikus -- I was his litmus test : being groomed as a child athlete / Tanya Prewitt-White -- Persist : homophobia in and survival through farm town high school sports / Lena A. Bequette -- 2/7/2016 : the morning I was raped / Ellie Arbetman -- "You're not a good cultural fit here" : being a woman in sports / Sara Erdner -- Experiencing same-gender and trans violence in sport / Jordan Forrest Miller -- I couldn't stay quiet / Shannon Mulcahy -- Experiencing sexual misconduct as a student-manager in intercollegiate athletics / Emily J. Tyler -- Athletic programmatic prevention : no more, not here, not within these walls / Tess M. Kilwein, Matt J. Gray, and Taylor Stuemky -- Title IX and sexual harassment in athletics / James H Bemiller -- Supporting survivors of sexual violence / Heather Imrie -- The "sex talk" is a continual conversation / Tanya Prewitt-White, Lauren Spirov, and Sarah Malone -- Moving forward : no more sweeping sexual misconduct under the rug / Tanya Prewitt-White.